ENGLISH LEARNERS’ INDONESIAN-ENGLISH TRANSLATION OF IDIOMATIC EXPRESSIONS WITHIN “MALIN KUNDANG” FOLKLORE: STRATEGIES, LOSS, AND GAIN - Raharjo, Yohanes Maria Restu Dian; Tarigan, Veronika Ita Karina (Universitas Bunda Mulia, 2025)
Translating idiomatic expression has been considered a complex challenge in translation training, particularly for English language learners in Indonesia who must navigate both linguistic and cultural differences between source and target languages. Departing from this issue, this study aims to investigate the strategies employed by English learners of Indonesia in translating idiomatic expressions from Indonesian into English, while also identifying the loss and gain within the translation results. This research employed a descriptive qualitative method. The data consisted of (1) Indonesian idiomatic expressions taken from folklore “Malin Kundang” and (2) ten student-produced English translations of the folklore. Content Analysis was employed to analyze the data by applying Baker’s (2018) framework of translation strategies for idioms and Larson’s (1998) concept of loss and gain in translation. The finding shows that there are four strategies employed by English language learners, namely (1) translation by paraphrase, (2) using an idiomatic expression of similar meaning but dissimilar form, (3) translation by omission of entire idiomatic expression, and (4) using an idiomatic expression of similar meaning and form. Among these strategies, translation by paraphrase emerged as the most frequently applied one, implicating that learner may possess sufficient knowledge of Indonesian idiomatic expressions but limited knowledge of their English counterparts. In addition, the cultural loss and compensation are identified as the most prominent phenomena of translation loss and gain in translation, especially the cultural loss. This indicates implementing “translation by paraphrase” most likely leads to successful meaning transfer at the cost of losing cultural nuance. Finally, this research highlights what translation strategies are appropriate for transferring Indonesian idiomatic expressions into English.